Control of tissue growth: elucidation of the Hippo signaling pathway - Pan, Duojia (Henry Stewart Talks, 2008)
Genetic screens for tumor suppressors in Drosophila, Identification of the Warts tumor suppressor, Identification of Hippo tumor suppressor and elucidation of the Hippo kinase cascade, Discovery of Yorkie as the nuclear effector of the Hippo pathway, Mechanism of Yorkie inactivation by phosphorylation, Conservation of the Hippo kinase cascade in mammals, The role of the Hippo pathway in mammalian organ size control and tumorigenesis
Reviewed at 2018/05/31